Pandarus cytuje Owidiusza w pierwszej księdze „Troilusa i Criseydy” Geoffreya Chaucera - Bobrowski, Antoni (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The medieval epic poem Troilus and Criseyde by Chaucer describes the history of unhappy love with the Trojan War in the background. The story is constructed in the convention of courtly love, and the author draws abundantly from a range of plot motifs preserved in the ancient literary tradition. The article discusses the way of intertextual use of Ovid’s Heroides 5 in the course of events told in Book One of the poem.